2018
DOI: 10.1021/acsami.8b10457
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Atomic Layer Deposition to Astronomical Optic Sizes: Low-Temperature Aluminum Oxide in a Meter-Sized Chamber

Abstract: Atomic Layer Deposition (ALD) is very attractive for producing optical quality thin films, including transparent barrier films on metal-coated astronomical mirrors. To date, ALD of mirror coatings has been limited to relatively small-sized substrates. A new ALD tool has been designed, constructed, and tested to apply uniform protective coatings over a 0.9 m diameter substrate in a 1 m diameter scale deposition plane. The new tool, which we have named the meter scale ALD system (MSAS), employs a unique chamber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…There are a plethora of different reactor designs and geometries that can be used to prepare ALD films, depending on the substrates to be coated. For example, the geometries can be adapted to coat a single or a large number of wafers, particles, or even astronomical mirrors . An integrated optimal ALD chamber design considers many geometry optimizations, such as the inlet tubes, the feed nozzles and showerhead, and of course the main chamber.…”
Section: Overview and Discussionmentioning
confidence: 99%
“…There are a plethora of different reactor designs and geometries that can be used to prepare ALD films, depending on the substrates to be coated. For example, the geometries can be adapted to coat a single or a large number of wafers, particles, or even astronomical mirrors . An integrated optimal ALD chamber design considers many geometry optimizations, such as the inlet tubes, the feed nozzles and showerhead, and of course the main chamber.…”
Section: Overview and Discussionmentioning
confidence: 99%
“…ALD processes are thus implemented at large-scale to protect 0.9 m wide Ag mirrors using Al 2 O 3 thin films [50]. It is shown that preservative coatings depend not only on the materials used but also on the deposition parameters such as T ALD or activation type because this latter can modify the intermediate layers [51][52][53].…”
Section: General Use Of Aldmentioning
confidence: 99%
“…Using Atomic Layer Deposition (ALD) for the protection of silver-based front surface mirrors was first reported by [5][6][7]. While compatible with substrates of large sizes, ALD is especially well suited for the protection of small to medium-sized front surface mirrors.…”
Section: Oxygen Plasma; Corrosion Barrier Introductionmentioning
confidence: 99%